Vitamin D Deficiency in Patients with Type 2 Diabetes Mellitus with and without Pulmonary Tuberculosis - Wahiduddin Wahiduddin; Agung Pranoto; Sudjarwo Sudjarwo (Journal of Public Health and Pharmacy)
Background: Vitamin D has a role in the body's calcium balance and immunodeficiency effects, and stimulates dendric cells, monocytes, T cells, macrophages in pathogenic microbes’ elimination. The variation occurrence as polymorphism on VDR might cause problem in production, transportation, and activity of vitamin D. The gap between the occurrence findings in previous studies shows that there are indication factors of VDR levels that probably associate with the T2DM range in comorbid with pulmonary tuberculosis. To determine vitamin D levels and factors associated with vitamin D deficiency in Type 2 Diabetes Mellitus (T2DM) patients with and without pulmonary Tuberculosis (TB).